2013 22nd International Conference on Noise and Fluctuations (ICNF) 2013
DOI: 10.1109/icnf.2013.6578985
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of low frequency noise and noise variability through CMOS bulk technology nodes

Abstract: Th-P-28International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…This trend is confirmed for a wide range of CMOS technology nodes between 0.12 μm and 20 nm ( Figure 5). Indeed, this figure shows the standard deviation of the logarithm of the normalized draincurrent noise versus the inverse of the square root of the device area for nMOS and pMOS transistors from six different technology nodes, that is, 0.12, 90 nm, 65 nm, 45 nm, 28 nm and 20 nm with gate oxide thicknesses between 8.5 and 1.3 nm [15]. The results revealed that the volumetric trap density for both nMOS and pMOS devices increases as the technology nodes are developed from 0.5 μm to 20 nm.…”
Section: C-noise Variability In Sio 2 Sion and High-k/metal Gate CMmentioning
confidence: 99%
“…This trend is confirmed for a wide range of CMOS technology nodes between 0.12 μm and 20 nm ( Figure 5). Indeed, this figure shows the standard deviation of the logarithm of the normalized draincurrent noise versus the inverse of the square root of the device area for nMOS and pMOS transistors from six different technology nodes, that is, 0.12, 90 nm, 65 nm, 45 nm, 28 nm and 20 nm with gate oxide thicknesses between 8.5 and 1.3 nm [15]. The results revealed that the volumetric trap density for both nMOS and pMOS devices increases as the technology nodes are developed from 0.5 μm to 20 nm.…”
Section: C-noise Variability In Sio 2 Sion and High-k/metal Gate CMmentioning
confidence: 99%
“…Recent deep submicron technologies increase defective components, mainly due to process variability [1], electromagnetic interferences, charge injection or radiation [2], or even cross talk effect [3]. Therefore, it is essential to provide support for dynamic faults using a circuit that detects and corrects faults, and additionally providing statistics to a high-level layer (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent submicron technologies provide more process variability increasing the quantity of defective components [2]. A defective router or link may ruin the mesh communication structure leading to an irregular topology (i.e.…”
Section: Introductionmentioning
confidence: 99%